Health information systems´ usability-related use errors in patient safety incidents - Eija Hautamäki; Ulla-Mari Kinnunen; Sari Palojoki (Finnish Social and Health Informatics Association, 2017)
Health information systems contain usability issues that cause use errors, which may pose a risk to patient safety. The aim of this study was to identify what kind of usability issues in information systems cause use errors that lead to patient safety incidents. Patient safety incidents reported into an incident reporting system in a Finnish hospital district during the year 2014 (n=2500) were analyzed from the perspectives of usability and use errors. An inductive content analysis was carried out in order to gather information about the usability issues that may have led to a use error, thus causing patient safety incidents. The results showed that the main usability issues are the distribution of information into multiple views, identification problems with the selected patient, and basic daily tasks' reliance on users' memory. The results show that the relationship between usability, use errors, and patient safety should be understood and considered in the health information system design.